Reconciling more than 150 years of taxonomic confusion: the true identity of Moenkhausia lepidura, with a key to the species of the M. lepidura group (Characiformes: Characidae) - Marinho, Manoela M. F.; Langeani, Francisco (Zootaxa, 2016)
Moenkhausia lepidura (Kner) is redescribed based on the examination of the type and other specimens from several localities of the Amazon and Orinoco basins. The species is readly diagnosed from congeners by a combination of a dark blotch on the upper caudal-fin lobe, lower lobe hyaline, and by the arrangement of predorsal scales, in which scales of anterior portion of predorsal area are arranged in pairs, followed by a single median row of scales extending to dorsal-fin origin. The analysis of the type material of Gymnotichthys hildae Fernández-Yépez and Knodus calliurus Ahl demonstrated the former is a junior synonym of Moenkhausia lepidura, whereas the latter should be removed from its synonymy. An identification key to the Moenkhausia lepidura-group is provided.